2010
DOI: 10.1111/j.1749-0774.2010.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer drug sensitivity testing using an oxygen electrode apparatus

Abstract: Conventional anticancer drug sensitivity testing methods, such as succinate dehydrogenase inhibition (SDI), histoculture drug-response assay (HDRA) and collagen gel droplet embedded culture drug sensitivity testing (CD-DST), all require primary culturing and are extremely complex tests that require considerable time for analysis. A major drawback of these methods is that if culturing is not performed properly, ambiguous results are produced. Therefore, we developed an oxygen electrode apparatus that uses cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Takahashi et al reported that the sensitivity of NOCS-1 cell lines established from mandibular gingival carcinoma and cell lines established by xenotransplantation of the cell lines were similar in anticancer drug susceptibility tests 28) . However, in all previous reports, the sensitivity of anticancer drugs is limited to single agents 28,29) . In the case of clinical administration, administer a combination of multiple drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Takahashi et al reported that the sensitivity of NOCS-1 cell lines established from mandibular gingival carcinoma and cell lines established by xenotransplantation of the cell lines were similar in anticancer drug susceptibility tests 28) . However, in all previous reports, the sensitivity of anticancer drugs is limited to single agents 28,29) . In the case of clinical administration, administer a combination of multiple drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer drug sensitivity of CDDP + 5-FU + DOC under normal contact concentrations was 10.8% for the T/C% of the primary tumor, 8.6% for NOKT-1, and 37.4% for NOKT-1-XG. Suzuki et al established cell lines from 15 patients with papillary tubular cancer and compared their susceptibility with that of primary tumors using anticancer drug susceptibility tests 29) . The cell lines and primary tumors demonstrated consistent susceptibility in 13 patients, while the primary tumor and established cell lines exhibited different sensitivities in 2 patients 29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All experiments were approved by the Institutional Ethics Committee of the School of Life Dentistry at Niigata, Nippon Dental University, and informed consents were obtained. Anticancer drug sensitivity testing using an oxygen electrode apparatus Anticancer drug sensitivity testing was carried out using the oxygen electrode apparatus described by the authors in a previous report and using the same evaluation method [11,12]. For the oxygen electrode apparatuses, we used the CT&C precision oxygen electrode apparatus (Aloka Co., Ltd.), which is capable of measuring single samples of a small number of cells, the DOX-10 (Daikin Industries, Ltd.), which is capable of measuring 10 samples using 2 9 10 6 cells/well, the DOX-24 (Aloka Co., Ltd.), which can measure 24 samples using 2 9 10 6 cells/well, and the DOX-96 (Daikin Industries, Ltd.), which can measure 96 samples using 2 9 10 5 cells/well.…”
Section: Culture Methodsmentioning
confidence: 99%
“…As a part of the precision medicine program, drug sensitivity screening has been more and more widely applied in recent years [ 11 , 12 ]. Although sensitive drugs of all the cancers could be screened theoretically, factors like finite cell number, the lack of tumor biopsy, and the high degree of heterogeneity in the tumor often result in unsatisfied clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%